Factors Affecting the Agricultural Sustainability of Wheat Farms in Kermanshah County - Reza Movahedi; Nafiseh Amiribavandpour; Karim Naderi Mahdeei (جغرافیا و پایداری محیط)
1- Introduction Inappropriate use of pesticides and fertilizers in Iran has led to severe damages on soil and water resources; reducing the fertility and performance of the lands, environmental contamination, and damages to the ecological cycle of nature and health problems for humans, animals and the environment. For this reason economic, social and cultural development programs after the Iran's revolution, the necessity of addressing this issue according to the standards and principles of sustainable development was highlighted. Despite some planning and measures taken in this regard, monitoring and evaluation of agricultural sustainability, the main dimensions of it, the factors relevant to sustainability, and selection the most suitable ways to move from the current status to the desirable situation is essential. Kermanshah is one of the most suitable areas for the development of agricultural activities, especially wheat cultivation; but any planning for sustainable development of agriculture in this city, needs an awareness of sustainable agricultural indices. On the other hand, with regard to this issue that wheat production among various agricultural products is considered as a fundamental and strategic commodity and plays an important role in preparing people's food needs; therefore the main purpose of this study was to analyze the factors affecting agricultural sustainability on wheat farms in Kermanshah County. 2-Materials and Methods The main purpose of this study is to review factors affecting agricultural sustainability on wheat farms in Kermanshah County. The research statistical population based on a surveying method consisted of irrigated wheat farmers who were working agriculture in Kermanshah County. Of those a number of 300 farmers were selected based on Kerjcie and Morgan table. A questionnaire was the main tool for data gathering. In addition to the questionnaire, interview technique also has used. Accuracy of indices and questions in the questionnaire or validity was verified by a group of experts. To determine the reliability of the questionnaire first 30 farmers completed the questionnaire then a Chronbach alpha test was used to calculate the results and it was 82 percent. To analyze data a number of different tests in particular multiple regression were used. 3- Resultsand Discussion Results showed that farmers' annual yield per hectare was 5.24 tones. The findings about the use of phosphate fertilizers (black) and nitrogen (White) also showed that farmers have used 100 to 300 kilograms per hectare of these fertilizers. About Potash fertilizer consumption, the majority of farmers (37.7 %) have used more than 200 kg per hectare. Findings from the use of pesticides and herbicides revealed that the majority of wheat has used one kg per hectare of these poisons. Results showed that there is a positive and significant relationship between the agro- technical factors, socio-economic factors and extension-educational factors as independent variables and dependent variable (the sustainability of agricultural farms). There was no significant relationship between policy and institutional factors with the sustainability of agricultural farms. This means that the sustainability of agricultural farms in the research region is not dependent to the policy and institutional factors. The results showed that the majority of farmers' farms (74.6%) were in the unsustainable situation. The results of correlations showed no significant relationship between age and education level with the dependent variable (sustainability of farms), but there was a significant relationship between performance and ownership variables with the sustainability of agricultural farms at level of one percent. The multiple regression results showed that variables include agri-technical, social and economic, and extension education factors could determine 50 percent of the agricultural sustainability variable. 4- Conclusion The results showed a significant relationship between the amounts of farms' sustainability and the yield per hectare, therefore it is recommended that the methods of sustainable farming be trained and educated to farmers with the aim of increasing yield per hectare and the farmers' income. Regarding to this result that the target farmers had a rather weak financial ability it is concluded that the governmental and non-governmental organizations should financially support the farmers by giving loans to those who operate according to sustainable agriculture items. In order to get better the sustainable farming operations, an extension and education course should be presented on farms about sustainable agriculture operations. Extension brochures and pamphlets also can be useful for better sustainable farming